Security and performance analysis of the SEAP authentication protocol in MANETs. (2017) - Maity, Soumyadev; Hansdah, R.C.
This paper describes and analyses a secure and efficient authentication protocol (SEAP) designed for mobile ad-hoc networks (MANETs). The SEAP protocol is a server coordination-based pairwise symmetric key management protocol which works on a hierarchical network architecture and supports dynamic membership. Besides, the protocol uses a passive external membership granting server (MGS) to provide stronger security. To ensure efficiency, the protocol uses only symmetric key cryptography, and to achieve storage scalability, it makes use of a pseudo random function (PRF). The protocol is also robust against authentication server (AS) compromise. We have formally proved the correctness of the security guarantees provided by the SEAP protocol using the strand space verification model. We have evaluated the proposed protocol using simulations on the QualNet simulator, and experimentations on a MANET testbed. Both simulation and experimental study demonstrate the effectiveness of the proposed protocol as compared to the other existing approaches.